2019
DOI: 10.1094/phyto-06-18-0188-r
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity ofPseudomonas syringaepv.actinidiaeStrains from Different Geographic Regions in China

Abstract: Pseudomonas syringae pv. actinidiae (Psa) causes kiwifruit bacterial canker (KBC), with a severe infection of the kiwifruit plant resulting in heavy economic losses. Little is known regarding the biodiversity and genetic variation of populations of Psa in China. A collection of 269 strains of Psa were identified from 300 isolates obtained from eight sampling sites in five provinces in China. The profiles of 50 strains of Psa and one strain of P. syringae pv. actinidifoliorum (Psaf) were characterized by Rep-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…According to our results, this phage can be used also against other Pseudomonas syringae pathovars, such as P. syringae pv. syringae , which are important phytopathogens for the agriculture sector because they can easily infect several horticultural plants [4,52,53,54,55,56], causing severe economic losses worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, this phage can be used also against other Pseudomonas syringae pathovars, such as P. syringae pv. syringae , which are important phytopathogens for the agriculture sector because they can easily infect several horticultural plants [4,52,53,54,55,56], causing severe economic losses worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies identified natural openings and lesions as important entry sites for Psa, as well as the importance of lenticels and fresh cut in the infection process, as observed through a scanning electron microscope [13,14]. Furthermore, it was observed, through bacterial injections into leaf veins as described by Serizawa and Ichikawa [15], that bacteria can migrate from young leaves to twigs facilitating a systemic infection throughout the vine [8,12,13,[16][17][18]. The bacterium was retrieved in xylem vessels and phloem tissues, indicating that the systemic spread can rapidly reach potentially any tissue of the infected plant [14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, after integrating this information and the numerous research results obtained so far, phylogeographical analyses were conducted; as a result, concrete scenarios of the origin and evolution of Psa are becoming apparent, as described below (e.g. Ushiyama, 1993;Sawada et al, 1997Sawada et al, , 1999Sawada et al, , 2002Sawada et al, , 2014bGenka et al, 2006;Mazzaglia et al, 2012;Butler et al, 2013;McCann et al, 2013McCann et al, , 2017Vinatzer et al, 2014;Bartoli et al, 2015;Ciarroni et al, 2015;Cunty et al, 2015b;Fujikawa & Sawada, 2016Baltrus et al, 2017;Vanneste, 2017;He et al, 2019).…”
Section: Origin and Evolutionmentioning
confidence: 99%